2012
DOI: 10.1292/jvms.11-0436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma-Oryzanol-Enriched Rice Bran Oil on Quality of Cryopreserved Boar Semen

Abstract: ABSTRACT. The aim of this study was to determine the effect of gamma-oryzanol-enriched -rice bran oil on the quality of cryopreserved boar semen. Ten boars provided semen of proven motility and morphology for this study. The semen was divided into three portions in which lactose-egg yolk (LEY) extender used to resuspend the centrifuged sperm pellet was supplemented with 2 types of rice bran oils, at a gamma-oryzanol concentration of 0 mg/ml of lactose egg yolk (LEY) freezing extender (group A, control), 0.1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
(82 reference statements)
0
27
0
Order By: Relevance
“…γ ‐oryzanol‐enriched rice bran oil also has positive effects on post‐thaw sperm quality (Kaeoket et al. ) and the required concentration depends upon the breed, the Duroc boars requiring lower concentrations than Large White and Landrace breeds (Chanapiwat and Kaeoket ).…”
Section: Cryopreservation Extendersmentioning
confidence: 99%
“…γ ‐oryzanol‐enriched rice bran oil also has positive effects on post‐thaw sperm quality (Kaeoket et al. ) and the required concentration depends upon the breed, the Duroc boars requiring lower concentrations than Large White and Landrace breeds (Chanapiwat and Kaeoket ).…”
Section: Cryopreservation Extendersmentioning
confidence: 99%
“…Several studies have shown moderate to quite dramatic effects of a variety of antioxidants on in vitro sperm quality. Antioxidants such as BHT (Roca et al 2004), polysaccharides (Hu et al 2013), rice bran oil (Kaeoket et al 2012), rosemary extract (Malo et al 2010) and fennel extract (Malo et al 2012) were able to improve most measures of post-thaw sperm fertility. Others have added the target molecules of the ROS and certain PUFAs in the freezing extenders to improve post-thaw sperm quality (Kaeoket et al 2010b).…”
Section: Cryopreserved Sperm Additivesmentioning
confidence: 99%
“…Recently, Kaeoket et al. () showed that supplementation of gamma‐oryzanol‐enriched rice bran oil in lactose–egg yolk (LEY) freezing extender resulted in an improvement of frozen–thawed Duroc boar semen qualities (i.e. progressive motility, viability and acrosome integrity).…”
Section: Introductionmentioning
confidence: 99%